Numerical Simulation on Heat Flow for Mixed Convection Within a Triangular Enclosure - Hossain, Muhammad Sajjad; Billah, MM; Bangalee, MZI; Alim, MA (GANIT: Journal of Bangladesh Mathematical Society, 2019)
Heat flow for laminar mixed convection in a triangular enclosure with uniformly heated bottom wall is solved using Galerkin weighted residual method of finite element formulation. A fluid with Prandtl number (Pr = 0.71) is also used to investigate the effects of heat flow for Reynolds number(40 ≤ Re ≤ 110) varying Rayleigh number (103≤ Ra ≤ 104) in that enclosure. In the enclosure, the left wall is considered cold; bottom wall is uniformly heated while the other inclined wall is insulated. The geometry of physical problems is represented mathematically by different sets of governing equations along with appropriate boundary conditions. Results are shown in terms of streamlines, isotherms, average Nusselt number and average temperature of the fluid in the cavity for uniform heating of bottom wall. It is seen that heat transfer rate from the heat source is higher for increasing value of Re. On the other hand, average bulk temperature declines significantly. It is also indicated that for fixed Prandtl number and various Ra, the buoyancy force and heat transfer rate inside the enclosure are increased for the greater value of Re. GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 27-43